Effect of Oil Spills Dispersant (OSD Green) Upon Tilapia Zilli - Khalaf, Manal K.; Beden, Mazin A.; Aziz, Nijim M. (Iraqi Journal of Aquaculture, 2021)
General Company for Ports of Iraq used (OSD Green) as a dispersant of oil. This type of dispersant has been tested for toxicity and effect on aquatic environment. The tests were occurred on (Tilapia) fish by applying different concentration of dispersant (200, 400, 600, 800, 1000 and1500 mg/l) to identify its toxicity and impact on Tilapia fish. It was found the lethal concentration is (300mg/l). Fish activity has been studied under sub lethal concentration and their effect on fish stress, based on the gills and fins movement. This type of dispersion treatment should be avoided unless critical situation as it’s harmful for aquatic environment and fish.